Customer attitudes and intention to support Islamic social enterprises in Indonesia : the influence of celebrity and credibility / Sri Rahayu Hijrah Hati - Hati, Sri Rahayu Hijrah (2015)
The study set out to examine the impact of social entrepreneur celebrity, social entrepreneur personal credibility and social enterprise organizational credibility on customer attitudes and intention to support social enterprises in Indonesia. The baseline model was developed to examine the impact of social entrepreneur personal credibility and social enterprise organizational credibility on attitudes and intention, while the competing model was developed to check the influence of the additional “celebrity” construct on both types of credibility, attitudes and intention. Data were collected both online and offline from 221 customers of the six largest Islamic social enterprises in Indonesia. Ads portraying leaders of these social enterprises were shown to their customers. Responses to the ads were then measured in terms of customers’ perceptions of social entrepreneur celebrity, social entrepreneur personal credibility and social enterprise organizational credibility, as well as customer attitude towards the ad and social enterprise brand, and their intention to continue supporting them in the future. Results from the structural equation modelling indicated that the effects of a) social entrepreneur personal credibility on attitude towards the ad, b) social entrepreneur organizational credibility on all three independent variables: attitude towards the ad, attitude towards the brand and support intention c) attitude towards the brand on support intention tend to be robust in both models and concur with previous research results. However, in contrast to some previous evidence, the current study found a direct link between social entrepreneur personal credibility and attitude towards the brand indicating a link between the endorser and the organization being endorsed. The hypothesis testing for the second model showed that the celebrity level of the endorser positively and significantly influenced the social entrepreneur personal credibility, social enterprise organization credibility, and attitude towards the ad and support intention. Attitude towards the brand was the only variable which was not influenced by the celebrity variable. The results showed that celebrity only has mediated effect on attitude towards the brand, and the effect is transmitted via both types of credibility: social entrepreneur personal credibility and social enterprise organization credibility. The study implies that brand is something that should be developed based on the credibility of the organization and endorser. In other words, attitude towards the brand cannot be influenced by the level of popularity of the endorser but rather, should be based on the trustworthiness, expertise and attractiveness of the endorser and trustworthiness and expertise in the organization. Despite being constrained to the Islamic social entrepreneurship research context, the current research has made contributions to social entrepreneurship through empirical evidence gained by examining it from marketing and customers’ perspectives.